2012
DOI: 10.5021/ad.2012.24.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis Due to Nondermatophytic Molds

Abstract: BackgroundAlthough there have been many studies about onychomycosis due to nondermatophytic molds (NDM), few studies about etiologic agents including NDM in onychomycosis have been reported in Korea. Objective: This study investigated onychomycosis due to NDM in the Gyeongju area of Korea.ObjectiveThis study investigated onychomycosis due to NDM in the Gyeongju area of Korea.MethodsIn the 10-year period from 1999~2009, we reviewed 59 patients with onychomycosis due to NDM. The etiologic agents were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
39
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 22 publications
9
39
0
5
Order By: Relevance
“…being the most common cause of NDM onychomycosis. This result is similar to those reported by Hilmioglupolat et al [20], Hwang et al [22], and Zaini et al [37]; however, our results differ from those reported in some other studies, for example Bonifaz et al [6] and Khosravi et al [24], who reported Scopulariopsis brevicaulis and Tosti et al [35] who reported Fusarium spp. as the principal etiologic agents.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…being the most common cause of NDM onychomycosis. This result is similar to those reported by Hilmioglupolat et al [20], Hwang et al [22], and Zaini et al [37]; however, our results differ from those reported in some other studies, for example Bonifaz et al [6] and Khosravi et al [24], who reported Scopulariopsis brevicaulis and Tosti et al [35] who reported Fusarium spp. as the principal etiologic agents.…”
Section: Discussionsupporting
confidence: 78%
“…The incidence of onychomycosis due to nondermatophyte (saprophytic) molds is increasing [11,33,37]. Factors contributing to this increase are damage of the nail surface during nail grinding or manicuring, use of artificial nails, advanced age, peripheral vascular diseases, diabetes, smoking and regular swimming [22,28]. Saprophytic onychomycosis can be caused by various fungi, including Scopulariopsis brevicaulis, Aspergillus spp., Fusarium spp., Acremonium spp., and Scytalidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…This species is also the most common human pathogen mainly associated with onychomycosis (Naidu et al., 1991, Stiller et al., 1992, Aspiroz et al., 2007, Latha et al., 2010, Tullio et al., 2010, Hwang et al., 2012, Lagacé and Cellier, 2012, Kim et al., 2013). In addition, some other indoor chaetomium-like species were also reported in clinical cases, such as D. funicola (= C. funicola , Koch & Haneke 1965), O. brasiliensis (= C. brasiliense , Hubka et al.…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium spp. have been reported frequently as common causative agents of NDM onychomycosis in Iran and other countries (6,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%